A sexualidade e o controle do corpo no Scivias e no causae et curae de Hildegarda de Bingen (Século XII) - Souza, Juliane Albani de (2013)
During the twelfth century, from the German empire, comes a Benedictine nun, Hildegard of Bingen (1098-1179) who would face a confrontation to change the socialpolitical situation of the empire through her writings. It would be a fight to reform the German Empire‘s laity and clergy which threatened to stain the structures of the Roman Church‘s Ecclesia. Hildegard puts herself in a Gregorian reformist perspective; although she lived a century after this movement has first started. Nevertheless, some problems would persist and affect the Church in Germany: the simony, and the nicolaism, the marriage of the priests, among other problems that disturbed Hildegard and other reformists. This research will deliberate on a small part of these reformists‘ issues, on those regarding the sexuality through Hildegard‘s perspective, in Scivias, and in Causae et curae. The point of view of a nun from the twelfth century about the sexuality shows contradictions and diversions in one of her texts. This research‘s goal is to comprehend Hildegard‘s perspective and show it to the readers. She conciliated two conceptions. One naturalistic which accepted the sexuality as a natural fact, and one more conservative, which saw in sexuality a mere tool for reproduction and raising the children. However, both conceptions were regarded with the Augustinian theses about the reproductive finality of conjugal sexuality. The gap between clergy and laymen is wide and Hildegard establishes a hierarchy which puts the clergy on top, for they distance themselves from the body fluids, the blood and the semen, the latter being nothing more than blood turned into semen due to the heat aggravated by carnal desires. The laymen, legitimated when married, are on the bottom of those who are able to be saved, but their merit is minimum and they will receive less on the end of time. The maximum merit is for the virgins and chastens, in other words, for the monks, followed by the celibatarian clergymen, provided that they obeyed the precepts and stayed in their orders